Інформаційний сервіс моніторингу серцево-судинної системи з можливістю сповіщення швидкої допомоги - Головачова, О. А. (ХНУРЕ, 2020)
Over the past 5 years, people are dying more and more from heart problems. Unfortunately, ambulances do not have time in time, and doctors cannot diagnose when a crisis occurs. Our system solves this issue. This is a smarter watch. As development technologies, the JAVA language was used, MySql is a database, in the future it is planned to transfer to the cloud. The system is tested for load using JMeter.
Keywords: моніторинг серцево-судинної системи; інформаційний сервіс